2023
DOI: 10.3390/jpm13030416
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol and CYP2D6: A Retrospective Cohort Study Evaluating Genotype-Based Outcomes

Abstract: Metoprolol is a medication commonly utilized in select patients to achieve a reduction in heart rate, systolic blood pressure, or other indications. A majority of metoprolol metabolism occurs via CYP2D6. Decreased expression of the CYP2D6 enzyme increases the concentration of metoprolol. Current pharmacogenomics guidelines by the Dutch Pharmacogenomics Working Group recommend slower titrations and dose decreases to minimize adverse effects from poor metabolizers or normal metabolizers taking concomitant medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The CYP2D6 genotype influences the pharmacokinetics of all these drugs. However, it is noteworthy that these pharmacokinetic variations predominantly manifest as differences in heart rate, as opposed to other response phenotypes such as hypertension [32,33]. Various studies -including those by Thomas and Johnson [30] and Cunningham and Chapman [34] -have underscored this distinction.…”
Section: β-Blockersmentioning
confidence: 99%
“…The CYP2D6 genotype influences the pharmacokinetics of all these drugs. However, it is noteworthy that these pharmacokinetic variations predominantly manifest as differences in heart rate, as opposed to other response phenotypes such as hypertension [32,33]. Various studies -including those by Thomas and Johnson [30] and Cunningham and Chapman [34] -have underscored this distinction.…”
Section: β-Blockersmentioning
confidence: 99%
“…This was validated in a systematic review and meta analysis by Blake et al [ 108 ]. These pharmacogenetic observations may have clinical relevance leading to adverse events (e.g., bradycardia), where those with poor metabolism genotypes have a significantly higher bradycardia event rate relative to those with normal metabolism genotypes [ 109 , 110 ]. Despite CYP2D6 contributing to the majority of metoprolol biotransformation, metoprolol did have a notable stereoselective effect.…”
Section: Genetic Determinants Of Beta Blocker Dispositionmentioning
confidence: 99%
“…CYP2D6 poor metabolizers have a higher risk of bradycardia because of their higher levels of metoprolol. 57 Haloperidol is also metabolized by CYP2D6. A study by Brockm€ oller and colleagues reported that the risk of pseudoparkinsonism was higher in poor metabolizers.…”
Section: Adrs and Pharmacogenomicsmentioning
confidence: 99%